Flipbook Sebagai Media untuk Meningkatkan Keterampilan Menulis Kembali Teks Non-fiksi pada Peserta Didik Kelas 5 Sekolah Dasar - Dewi, Indah Rosalina; Masjid, Akbar Al Masjid; Praheto, Biya Ebi; Trisharsiwi, Trisharsiwi (Piramida Akademi, 2023)
Writing is the most complex language skill, because writing skills involve proficiency in language selection, pouring logical and structured ideas. Writing skills in grade 5A students of SD Negeri Jomblangan are still relatively low. The purpose of this study is to improve the skills of rewriting nonfiction texts using flipbook media. This research uses Classroom Action Research, which consists of two cycles and consists of four main steps, namely planning, implementation, observation and reflection. Data collection techniques in this research include interviews, observation, tests, and documentation. Data analysis used quantitative and qualitative descriptive. The research results showed that, as seen in each research cycle, the skills of class 5 A students in rewriting nonfiction texts were improved by using flipbook media. The average score of students in cycle I rewriting nonfiction texts was 68.03 with a classical completeness level of 53.57%. In cycle II there was an increase in value, namely 79.82 with a classical completion level of 82.14%. For activities in cycle I, students obtained a score of 67.19% and in cycle II it increased to 90.63%. The conclusion of this research is that students in class 5 A of Jomblangan State Elementary School can effectively improve their skills in rewriting nonfiction texts using flipbook media.